Analyser l’évolution des pratiques sportives en montagne peu aménagée à partir des données de fréquentation des cabanes. Application aux Alpes Valaisannes - Jacques Mourey; Christophe Clivaz; Philippe Bourdeau (Revue de Géographie Alpine)
Mountain sports (skiing, mountaineering, hiking, etc.) play an important role in the restructuring and diversification of tourism in the Alps. However, the transformation of these practices is subject to a significant lack of information, especially concerning how many people visit the "less-developed" mountains, outside the urban centres that make up the resorts. For mountain areas, there is specific data for mountain huts (term used in Switzerland), or refuges (term used in France). This data shows the location and the number of visitors of "less-developed" mountain areas, allowing to study the transformation of outdoor sports in these sectors. However, this data is not always easily accessible, especially over a long period of time, and it presents several biases. In this paper, we discuss the interest and the limits of the data on visitor numbers in mountain huts in Switzerland and in France for the study of the change of visitor numbers in the "less-developed" mountains and more particularly of the sporting practices which take place there. An example of analyses, based on statistical processing of the number of overnight stays, as well as semi-structured interviews with hut keepers and owners, will be presented for a sample of huts in the Valais Alps (Switzerland). This analysis allowed us to confirm (i) the general decline in the number of mountaineers visiting the high mountains in summer, with an 11% drop in the number of overnight stays between 1995-98 and 2016-19 in the 8 huts studied; (ii) the concentration of mountaineers on technically easy and/or emblematic and/or quickly accessible routes; and (iii) the development of ski touring, with a 6% increase in the number of overnight stays in spring between 1995-1998 and 2016-2019.